Dynamics of sodium channel Na(v) 1.5 expression in astrocytes in mouse models of multiple sclerosis - Pappalardo, Laura W. (2014)
Astrocytes actively participate in the central nervous system (CNS) response to injury, including in multiple sclerosis (MS). Astrocytes can play both beneficial and detrimental roles in response to neuroinflammation, however in extreme cases astrogliosis can result in the formation of a glial scar, which can impede the regeneration of injured neurons. While astrocytes do not express voltage-gated sodium channel Na(v)1.5 in nonpathological human brain, they exhibit robust upregulation of Na(v)1.5 within acute and chronic MS lesions. Recent work indicates that Na(v)1.5 contributes to the pathways that regulate glial scar formation in vitro via modulation of intracellular Ca(2+). However, the temporal dynamics of astrocytic Na(v)1.5 channel expression in response to neuroinflammatory pathologies have not been investigated. We examined astrocytes from mice with monophasic and chronicrelapsing experimental autoimmune encephalomyelitis (EAE) by immunohistochemistry to determine whether Na(v)1.5 is expressed in these cells, and whether the expression correlates with severity of disease and/or phases of relapse and remission. Our results demonstrate that Na(v)1.5 is upregulated in astrocytes in situ in a temporal manner that correlates with disease severity in both monophasic and chronic-relapsing EAE. Furthermore, in chronic-relapsing EAE, Na(v)1.5 expression is upregulated during relapses and subsequently attenuated during periods of remission. These observations are consistent with the suggestion that Na(v)1.5 can play a role in the response of astrocytes to inflammatory pathologies in the CNS and suggest Na(v)1.5 may be a potential therapeutic target to modulate reactive astrogliosis in vivo.